Leaf water diffusion dynamics in vivo through a sub-terahertz portable imaging system. (May 2020) - Girolamo, F V Di; Toncelli, A; Tredicucci, A; Bitossi, M; Paoletti, R
Abstract: The development of terahertz based technology has given the opportunity for the realization of non destructive techniques capable of gaining meaningful information on delicate systems such as biological samples. Here, the health status of leaves in vivo has been monitored through a portable terahertz imaging system. The data have been extracted and analysed from the images acquired and compared with analogous results reported in the literature on similar systems. The possibilty of extracting additional information from the images regarding leaf details has also been explored.